HUBUNGAN KETERAMPILAN KOMUNIKASI DENGAN AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VIII SMP NEGERI 3 PAGUYAMAN - Sri Rahmita Antu; Radia Hafid; Mamang Kasim; Frahmawati Bumulo; Fatmawaty Damiti (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to examine the relationship between communication skills and students’ learning activities in Social Studies for eighth-grade students at SMP Negeri 3 Paguyaman. The research employed a quantitative approach using a descriptive correlational design. The population of this study consisted of all eighth-grade students, with a sample of 30 students selected based on appropriate sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability. Simple linear regression analysis was applied to analyze the relationship between communication skills and students’ learning activities. The results indicate a positive and significant relationship between communication skills and learning activities in Social Studies. This is evidenced by a significance value of 0.000, which is lower than the significance level of 0.05. These findings suggest that better communication skills contribute to higher levels of student learning activity during the instructional process. Furthermore, the coefficient of determination of 0.458 indicates that communication skills account for 45.8% of the variance in students’ learning activities, while the remaining 54.2% is influenced by other factors not examined in this study. Therefore, enhancing students’ communication skills is essential in fostering active learning in Social Studies classrooms.